Penerapan Sistem Pengupahan Buruh dan Dampaknya Bagi Kesejahteraan Buruh di CV Anugrah Bangun Sejahtera Sragen - Marfuah, Asti; , Shalman Al Farizi, S.H., M.Kn (2017)
This study aims to determine the application of the sistem to determine wage CV Anugrah Bangun Sejahtera in conjunction with government policy on wage and to investigate the implementation of the wage sistem in CV Anugrah Bangun Sejahtera, workers/laborers can obtain the necessities of life is worth it or not. This research method using empirical juridical approach with primary data in the form of interviews and secondary data from the materials library. Data were collected by literature study and field study with qualitative data analysis. These results indicate that (1) the application of the wage sistem uses fixed wage sistem in accordance productivity and wage sistems time period (2) the implementation of the sistem of workers / laborers are not acquiring the rights and welfare of their need for decent living.